Development and characterization of novel magnesium oxide nanoparticle-impregnated chitosan-based guided tissue regeneration membrane – An in vitro study - Johnisha Harris; Kaarthikeyan Gurumoorthy (Journal of Indian Society of Periodontology)
Introduction: Although a lot of commercially available guided tissue regeneration (GTR) membranes are used, none of them could actually ensure complete bone regeneration so far and they also have certain limitations. This study aims to explore further and develop a membrane that might overcome these limitations and aid in bone regeneration for the treatment of bony defects. Materials and Methods: Magnesium oxide nanoparticles (MgONPs) were prepared from magnesium nitrate prepared by calcination at different temperatures and dried using filter paper under specific temperature. Later, 0.3 ml of 0.2 M 1% acetic acid was added to water and placed in the stirrer for at least 1 h. Chitosan (CS) (2%) of two different concentrations containing 0.588 g and 0.576 g of CS, respectively, was prepared and added to the previous mixture. To these concentrations, the prepared MgONPs were added and stirred using a magnetic stirrer for 1 h. Later, it was cast in the mold and dried. The prepared membrane was immersed in 1 M sodium hydroxide to neutralize acetic acid. After preparation, they were subjected to scanning electron microscope (SEM) analysis, energy-dispersive X-ray (EDAX), Fourier transform infrared spectroscopy (FTIR), and contact angle test. Results: In SEM analysis, spherical in size, uniformly dense, and porous agglomeration was noticed. EDAX and FTIR revealed the formation of MgONPs (magnesium oxide) in the membrane. The average contact angles of the CS with MgONPs and control membranes were 85.48° and 80.80°, respectively. Degradation analysis showed that test membrane showed a slower degradation rate than control collagen membrane at the end of the 28th day. Conclusion: On comparing membranes with pure CS, membranes with nanoparticles, and control collagen membranes, the membrane incorporated with nanoparticles showed more favorable positive outcomes.